FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN DI PERUSAHAAN JAKARTA ISLAMIC INDEX (JII) TAHUN 2018-2022 - Mellya Embun Baining; Neneng Sudharyati; Al Akrom Alparidi (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The aim of this research is to determine the influence of Intellectual Capita, Good Corporate Governance, Accounting Conservatism on finance with company size as a moderating variable in companies registered on the Jakarta Islamic Index (JII) 2018-2022. Data used is quantitative source secondary data company financial reports for 2018-2022. Data analysis uses multiple linear regression and hypothesis testing. The research results obtained were that Intellectual capital and accounting conservatism had a significant effect on ROA in companies listed on (JII) 2018-2020, while good corporate governance had no significant effect on ROA in companies listed on (JII) 2018-2020. Intellectual capital has a significant effect on ROA with company size as a mediating variable in companies listed (JII) 2018-2020. Meanwhile, good corporate governance and accounting conservatism do not have a significant effect on ROA with company size as a mediating variable in companies listed (JII) for 2018-2020.